Values education in England and Wales... - Mike Fearn; Leslie Francis (Jesuit University Ignatianum in Krakow, 2017)
This paper demonstrates that practical theology can make an important contribution to values education. Following an introduction to the values education framework within England and Wales, attention is focused on a case study which illustrates the sexual values of young people. This illustration makes available a seminal study published in the English language to a Polish audience and shows the extent to which practical theology can inform values education.